Feasibility and improvement of a three-dimensional printed navigation template for modified cortical bone trajectory screw placement in the lumbar spine - Shi, Wenjie; Aini, Mijiti; Dang, Limin; Kahaer, Alafate; Zhou, Zhihao; Wang, Yixi; Maimaiti, Abulikemu; Wang, Shuiquan; Guo, Hailong; Rexiti, Paerhati (Frontiers in Surgery, 2022)
Objectives: Compared with traditional pedicle screw trajectory, cortical bone trajectory (CBT) increases the contact surface between the screw and cortical bone where the screw is surrounded by dense cortical bone, which does not deform remarkably due to degeneration. We aimed to provide detailed information about the improvement of three-dimensional (3D)-printed navigation templates for modified CBT screw placement in the lumbar spine and evaluate the safety and accuracy thereof. Methods: Four human cadaveric lumbar spine specimens were selected. After CT scanning data were reconstructed to 3D models, either the left or right side of each specimen was randomly selected to establish a 3D-navigation template, mutually complemented with the surface anatomical structure of the lateral margin of the lumbar isthmus, vertebral plate, and spinous process. The corresponding 3D centrum was printed according to the CT scanning data, and a navigation template of supporting design was made. The same template was used to insert CBT screws into 3D printed and cadaveric specimens. After the screws were inserted, the screw path of the 3D printed specimens was directly observed, and that of the anatomical specimens was scanned by CT, to determine the position and direction of the screws to analyze the success rate of screw placement. Results: Twenty cortical bone screws were placed in each of the 3D printed and anatomical specimens, with excellent rates of screw placement of 100% and 95%, respectively. Conclusions: We report the easy, safe, accurate, and reliable use of a 3D-printed navigation template to carry out screw placement by modified cortical bone technique in the lumbar spine.